Neuroinflammatory mechanisms in amyotrophic lateral sclerosis pathogenesis. Issue 5 (October 2018) - Thonhoff, Jason R.; Simpson, Ericka P.; Appel, Stanley H.
Abstract : Purpose of review: Neuroinflammation is increasingly recognized as an important mediator of disease progression in patients with amyotrophic lateral sclerosis (ALS), and is characterized by reactive central nervous system (CNS) microglia and astroglia as well as infiltrating peripheral monocytes and lymphocytes. Anti-inflammatory and neuroprotective factors sustain the early phase of the disease whereas inflammation becomes proinflammatory and neurotoxic as disease progression accelerates. Initially, motor neurons sustain injuries through multiple mechanisms resulting from harmful mutations causing disruptions of critical intracellular pathways. Injured motor neurons release distress signal(s), which induce inflammatory processes produced by surrounding glial cells in the CNS as well as peripheral innate and adaptive immune cells. This review will focus on mechanisms of neuroinflammation and their essential contributions in ALS pathogenesis. Recent findings: Regulatory T lymphocytes (Tregs) are a subpopulation of immunosuppressive T lymphocytes that become reduced and dysfunctional as the disease progresses in ALS patients. Their degree of dysfunction correlates with the extent and rapidity of the disease. Treg numbers are boosted in transgenic mutant SOD1 (mSOD1) mice through the passive transfer of Tregs or through treatment with an interleukin-2/ interleukin-2 monoclonal antibody complex and rapamycin. Treating the transgenic mice with either of these modalities delays disease progression and prolongs survival. In addition, Treg function is restored when dysfunctional Tregs are isolated from ALS patients and expanded ex vivo in the presence of interleukin-2 and rapamycin. Based on these findings, a first-in-human phase 1 trial has been completed in which expanded autologous Tregs were infused back into ALS patients as a potential treatment. The infusions were safe and shown to 'hit target' by enhancing both Treg numbers and suppressive functions. Summary: A delicate balance between anti-inflammatory and proinflammatory factors modulates the rates of disease progression and survival times in ALS. Tipping the balance toward the anti-inflammatory mediators shows promise in slowing the progression of this devastating disease.